Latin America: Education, Knowledge and Competitiveness - Andere, Eduardo M. (Education Policy Analysis Archives, 2004)
This article attempts to demonstrate that Latin America faces a somber future in its external trade and external investment because it doesn?t support education and knowledge production and distribution as key strategies in a highly competitive global world. This article will contend that Latin America is not ready for global and international competition, and that the strategy of opening the national economies and their deregulation were not enough to create a model of sustainable development.